An Investigation into the Impact of Religion on Health among Iranian Community Residents in the UK - Ghazi, Fery; Caldwell, Kay; Collins, Leila; Workman, Elizabeth (Implicit Religion, 2003)
The primary aim of this study is to explore the interrelationships between health, health beliefs and religious beliefs within the Iranian community resident in the UK. The theoretical framework used for this study draws on the work of the existentialists who describe human existence in terms of four dimensions—the physical world, the social world, the public world and the spiritual world. A purposive convenience sample was selected, by nominated and network qualitative sampling techniques, representing the main Iranian religious groups. A qualitative, phenomenological approach to data collection was employed, semi-structured focus group interviews being conducted with four groups, each representing one of the main religious groups within the Iranian community. All interviews were audio-recorded and transcribed, and content analysis was carried out utilising Huberman’s systematic approach as a framework. Five major themes emerged from the analysis of the focus group interviews. First was the process by which a system of values was constructed. Second was the issue of the continuum of cultural integration/isolation. Third was the level at which social cohesion or division was experienced. Fourth was the concept of spirituality as a coping strategy and fifth was the ebb and flow of religious influence over the lifespan. Consideration was given to these themes, and the ways in which they interrelated and overlapped. This led to the conclusion that cultural and religious identity were experienced and perceived differently, but recognised to be interrelated. Spirituality appeared to be more strongly related to health, in its broadest sense, than did religiosity, and well-being and health were viewed as being inextricably linked. The relevance of this study to health care practice is evident. Consideration of the spiritual dimension of care must extend beyond attention to religious practices, and the potential exists for the coping strategies related to spirituality to be developed as an aid to therapeutic intervention.